2017
DOI: 10.1111/eje.12296
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Special Needs Dentistry education and practice amongst Australian dental auxiliary students

Abstract: DH/DT/OHT students' comfort levels, positive attitudes and supportiveness for SND suggested positive implications for these practitioners to partake in multidisciplinary management of patients with special needs, thus indicating the need for standardised training requirements and practice guidelines in this area of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…Usefulness of the practical part of the research was found satisfactory by 83.7% of the students. This goes in agreement with several previous studies [ 9 , 37 , 38 ] that reported the importance of undergraduate students training and the high level of satisfaction the students report when they receive such educational experiences during their early academic years. Furthermore, early contact with the patients might aid dental students developing their practical and team working skills.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Usefulness of the practical part of the research was found satisfactory by 83.7% of the students. This goes in agreement with several previous studies [ 9 , 37 , 38 ] that reported the importance of undergraduate students training and the high level of satisfaction the students report when they receive such educational experiences during their early academic years. Furthermore, early contact with the patients might aid dental students developing their practical and team working skills.…”
Section: Discussionsupporting
confidence: 93%
“…The high prevalence of oral diseases reported amongst people with special health needs highlights the need for an increased intervention in providing preventative, emergency, definitive and long-term oral health care. Therefore, it is imperative for dental students and dental professionals to be adequately trained and acquire a strong basis in delivery of care to those patients to alleviate the increased oral disease burden and unmet treatment needs for such patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, special needs dentistry should become part of the final state examinations all dental students in this country have to pass in order to get the licence for practicing dentistry. Apart from dentists, also curricula for dental auxiliary students should be developed as active participation of dental hygiene, dental therapy and oral health therapy practitioners in the care of patients with special needs can also help improve patients' oral health statuses and their access to oral healthcare services …”
Section: Discussionmentioning
confidence: 99%
“…There is growing advocacy in Australia and internationally to improve the training of oral health professionals to ensure the dental workforce appreciates the needs of these individuals and has the skills to confidently address them 2,11–18 . However, little is known of what clinicians find challenging about managing this group of individuals and whether additional support would improve their willingness to treat those with special needs 8 .…”
Section: Introductionmentioning
confidence: 99%